Relation between out-of-home eating and weight status in adolescents living in Sicily, southern Italy - Mistretta, Antonio; Marventano, Stefano; Zappalà, Gaetano; Currenti, Walter; Matalone, Margherita; Marranzano, Marina (Progress in Nutrition, 2019)
Overweight and obesity have increased dramatically over the last decades becoming the leading public health issue of the modern era. The transition from a traditional dietary patterns to a “Westernized” pattern, including consumption of fast-processed foods, “junk” foods and sweet beverages contribute to the development of overweigh and obesity. The aim of this study was to evaluate the relation between out of home eating and metabolic parameters in adolescents living in a Mediterranean area. The study had a cross-sectional design. Data were collected during two scholastic years (2012-13 and 2013-14) on 1643 adolescents of 13–16 years attending 15 secondary schools randomly selected in the urban area of the municipality of Catania. Demographic characteristics, physical activity status and eating habits were collected though a validated questionnaire and then the KIDMED score was calculated. Weight status was assessed by medical visit. Out-of-home eating was associated with being obese (OR 1.15, 95% CI: 1.01-1.15), especially when occurring for a main meal rather than for snack (OR 1.07, 95% CI: 1.02-1.22). These results were no longer significant after the adjustment for KIDMED score. Moreover, having a good adherence to Mediterranean diet was associated with 6% decreased odds of being obese (OR 0.94, 95% CI: 0.89-0.99). Adolescent eating out more than once per week were eating significantly less fruit and vegetables and more fast-foods and sweetened beverages. In conclusion, out-of-home eating is associated with unhealthy dietary choices among adolescents living in a Mediterranean country. The promotion of alternative nutritious snacks (such as nuts, fresh fruit and vegetables) in school setting should be considered.